Social Health and its Related Factors among Medical Students of Kerman University of Medical Sciences in 2017 - Ali Khalooei; Seedeh Maryam Karamatili (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Social health as one of the dimensions of health shows the status of the correct perception of the community, having proper social roles and functions. The purpose of this study was to determine the status of social health and its related factors in medical students of Kerman University of Medical Sciences. Materials and Methods: This is a cross-sectional descriptive and analytical study. By census method, 666 medical students of Kerman University of Medical Sciences were studied in the winter of 2017. The instrument used to measure social health was the Keyes questionnaire. The data were entered SPSS-22 software and Independent t test, ANOVA, post-hoc tukey test, multiple linear regression, Person and Superman correlation were used for analyzing data. Results: The mean social health score of the students was 57.2 (9.4). Social integration 71.6 (17.4) and social acceptance 42.1 (14.7) had the highest and the lowest (42.1) mean scores, respectively. Social health had positive correlation with levels of interest in the field of study (P=0.000, r=0.286), mental health (P=0.000, r= 0.267) and physical health (P=0.000, r= 0.188), but it had a negative correlation with Concerns about the job prospects (P=0.000, r=-0.200). Multivariate linear regression analysis showed that five independent variables, including: interest in the field of study (B=3.56), mental health (B=3.06), membership non-governmental organizations (B=1.68), physical health (B=1.23), and concern about the job prospects (B=-1.47), as predictive variables were explained 16.6 of social health scores. Conclusion: This study showed that social health of medical students is not appropriate. Then social acceptance in comparison with other dimensions, with the lowest score, was more unfavorable. Social, health, as one of the important dimensions of health that indicates the status of social roles playing and social functions, including job performance. Therefore, special attention is needed to improve this dimension of health. DOI: http://doi.org/10.22037/ch.v5i4.19645